2016
DOI: 10.1055/s-0036-1593374
|View full text |Cite|
|
Sign up to set email alerts
|

Neurological Manifestations in Familial Mediterranean Fever: Results of 22 Children from a Reference Center in Kayseri, an Urban Area in Central Anatolia, Turkey

Abstract: Familial Mediterranean fever (FMF) is an inherited inflammatory disorder characterized by attacks of fever with polyserositis. The purpose of this study was to evaluate pediatric patients with FMF who had central nervous system (CNS) findings. Our medical records database for 2003 to 2014 was screened retrospectively. In total, 104 patients with FMF were identified, 22 of whom had undergone neurological examination for CNS symptoms. Neurological findings included headache in 16 patients (72.7%), epilepsy in 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
4
12
3
Order By: Relevance
“…Looking in more detail on neurological manifestations in patients w/o MS, headache was the most prevalent symptom among low-penetrance variant carriers irrespective of the underlying genotype. This finding demonstrates a similar result compared to AID patients carrying disease-causing variants, of whom headache syndromes were also reported at a high frequency such as 84% of CAPS and 72% of FMF patients [12,39]. A greater proportion of patients with NLRP3 variants showed CN affection, which supports findings of our previous study and underscores the vulnerability of cranial nerves to inflammation caused by NLRP3-associated inflammasome activation [24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Looking in more detail on neurological manifestations in patients w/o MS, headache was the most prevalent symptom among low-penetrance variant carriers irrespective of the underlying genotype. This finding demonstrates a similar result compared to AID patients carrying disease-causing variants, of whom headache syndromes were also reported at a high frequency such as 84% of CAPS and 72% of FMF patients [12,39]. A greater proportion of patients with NLRP3 variants showed CN affection, which supports findings of our previous study and underscores the vulnerability of cranial nerves to inflammation caused by NLRP3-associated inflammasome activation [24].…”
Section: Discussionsupporting
confidence: 88%
“…This was underscored by a high number of abnormal MRI and CSF findings in those patients. CNS inflammation is often observed in patients with pathogenic NLRP3 mutations but has also been reported in patients with MEFV mutations [5,12,14,15,39,40]. Regarding NLRP3, neurological involvement was so far reported for 40-95% of CAPS patients and has mainly been linked to the pathogenic R260W mutation of the NLRP3 gene, while the V198M variant was negatively associated with neurological involvement [12,13,35].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Canpolat et al 21 of 22 children with FMF showed neurological findings included headache in 16 patients (72.7%), epilepsy in six patients (27.3%), pseudotumor cerebri in two patients (9.1%), multiple sclerosis in one patient (4.5%), and tremor in one patient (4.5%). The most common MEFV gene mutation in these patients was M694V (40.9%).…”
Section: Discussionmentioning
confidence: 93%
“…Few cases were detected in the literature about FMF and MS coexistence. Most of these reports do not provide any information about immunomodulating/immunosuppressive therapies for MS. [5][6][14][15][16] In some cases, therapies for MS were reported while their effects on FMF attacks were not. 17,18 Ceylan et al 19 reported two cases of FMF with MS. MS diagnosis was established by cervical MRI findings and oligoclonal band results in one case and by cranial MRI findings in the other case.…”
Section: Discussionmentioning
confidence: 99%